ДА ЛИ СЕ КРЕИРАЊЕ ЈАВНИХ ПОЛИТИКА РАЗВИЛО У РАВНОПРАВНУ ФУНКЦИЈУ ЈАВНЕ УПРАВЕ У РЕПУБЛИЦИ СРБИЈИ? - Vučetić, Dejan; Atanasijević, Jasna (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
This paper examines the role of public policy making by public administration in Serbia as one of the fundamental functions of public administration. By analyzing the normative framework and its application, the paper explores how it developed throughout history and in recent decades. A  set of regulations from 2018, including the Law on Planning System and accompanying bylaws  on methodology for policy making, have laid the foundation for modern, evidence-based public policy in Serbia. Using qualitative methods, including normative-dogmatic and document analysis, the study provides the review of the developments so far and recommendations for further strengthening of this function of public administration in Serbia.
Keywords: Public policy; public administration; governance; Serbia; reform; normative framework; effectiveness